On the motivational nature of cognitive dissonance dissonance as psychological discomfort - Elliot, Andrew J.; Devine, Patricia G. (1994)
Most empirical research investigating the motivational properties of cognitive dissonance has focused on the arousal component of dissonance rather than on the psychological component explicitly delineated by L. Festinger (1957). In 2 induced-compliance experiments, a self-report measure of affect was used to demonstrate that dissonance is experienced as psychological discomfort and that this psychological discomfort is alleviated on implementation of a dissonance-reduction strategy, attitude change. Experiment 1 yielded supporting evidence for both of these propositions. Experiment 2 replicated the 1st experiment and ruled out a self-perception-based alternative explanation for the dissonance-reduction findings in Experiment 1. Results from the 2 experiments strongly support Festinger's conceptualization of cognitive dissonance as a fundamentally motivational state.